2023
DOI: 10.1371/journal.pcbi.1010804
|View full text |Cite
|
Sign up to set email alerts
|

Community composition exceeds area as a predictor of long-term conservation value

Abstract: Conserving biodiversity often requires deciding which sites to prioritise for protection. Predicting the impact of habitat loss is a major challenge, however, since impacts can be distant from the perturbation in both space and time. Here we study the long-term impacts of habitat loss in a mechanistic metacommunity model. We find that site area is a poor predictor of long-term, regional-scale extinctions following localised perturbation. Knowledge of the compositional distinctness (average between-site Bray-Cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The analogous argument was developed by Purves and Pacala (2005) and Chisholm and Pacala (2010) in the context of SADs. This observation makes it plausible why we previously found the log‐series OFD predicted by the LSPOM in simulations of the Lotka‐Volterra Metacommunity Model (LVMCM), where the abiotic environment varies from site to site (O'Sullivan et al, 2023).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The analogous argument was developed by Purves and Pacala (2005) and Chisholm and Pacala (2010) in the context of SADs. This observation makes it plausible why we previously found the log‐series OFD predicted by the LSPOM in simulations of the Lotka‐Volterra Metacommunity Model (LVMCM), where the abiotic environment varies from site to site (O'Sullivan et al, 2023).…”
Section: Discussionmentioning
confidence: 59%
“…For further discussion on the relationship between the two models, see Supplementary Section S10. We note that in a recent study (O'Sullivan et al, 2023) we showed that the LSPOM can be fit to two additional datasets describing occupancy lichen-fungi and in assemblages of lake-living diatoms. We also showed that LVMCM simulations with environmental heterogeneity and local richness distributions matching these empirical datasets have occupancy structures that can be modelled using the LSPOM framework.…”
Section: Con Clus Ionsmentioning
confidence: 73%
“…To understand credit responses to interventions large scale computational simulations of complex ecological assemblages have been employed, utilising the Lotka-Volterra Metacommunity Model (LVMCM). This established, spatially explicit, multi-layered metacommunity simulation model can reproduce a variety of macro-ecological patterns, including recreating occupancy frequency distributions or strongly rightskewed range size distribution (26)(27)(28). For a further detailed description of the LVMCM please refer to the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…To accurately simulate the impact of small habitat alterations on landscape-level biodiversity outcomes, a sophisticated spatially explicit model is required (26)(27)(28). The model incorporates multiple hierarchical elements.…”
Section: Detailed Description Of the Lvmcmmentioning
confidence: 99%
“…For example, while in some contexts increasing the spatial connectivity among communities enhances INNS establishment (Chapman et al 2020), in others it may also enhance community resistance to invasion (Cadotte 2006;Grainger and Gilbert 2016;Howeth 2017). Also, whereas β-diversity patterns explain why some fragmented plant communities go through an increase in species richness after invasion events (O'Sullivan et al 2023), the opposite can also occur (see also Peng et al 2019;Jauni and Hyvönen 2012;Fridley et al 2007). To address these challenges, studies need to be based on hypotheses, sampling designs and variables that explicitly consider multiscale phenomena (Schiesari et al 2019;Patrick et al 2021).…”
Section: Introductionmentioning
confidence: 99%